2021
DOI: 10.1101/2021.02.23.432493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GPI-anchored FGF directs cytoneme-mediated bidirectional signaling to self-regulate tissue-specific dispersion

Abstract: During development, a handful of signals sculpt diverse tissue architectures. How the same signal produces different tissue/context-specific information and outcomes is poorly understood. We explored the basis that programs tissue-specific FGF dispersion and interpretation by cytoneme-mediated contact-dependent communication. Although a Drosophila FGF was thought to be freely secreted, we discovered that it is glypiated and GPI-anchored on the source cell surface, which inhibits non-specific secretion but faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 88 publications
1
7
0
Order By: Relevance
“…Moreover, Pyr is apically enriched within the source cell 50 . We predict that the membrane tethering is critical to control cytoneme-mediated Pyr signaling, similar to what was observed for a GPI-anchored FGF, Branchless that controls Drosophila ASP development 21 . Similarly, apical enrichment of Ths:GFP suggests a spatial asymmetry in the Ths release.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Moreover, Pyr is apically enriched within the source cell 50 . We predict that the membrane tethering is critical to control cytoneme-mediated Pyr signaling, similar to what was observed for a GPI-anchored FGF, Branchless that controls Drosophila ASP development 21 . Similarly, apical enrichment of Ths:GFP suggests a spatial asymmetry in the Ths release.…”
Section: Discussionsupporting
confidence: 72%
“…Cytoneme-deficiency in AMPs caused pupal lethality, which might suggest that the contact-dependent signaling via cytonemes plays an important role in muscle development/homeostasis. Moreover, a recent study showed that cytonemedependent FGF-FGFR interactions between the ASP and wing disc induces bidirectional responses 21 . It is likely that similar cytoneme-dependent bidirectional receptor-ligand interactions can simultaneously control both wing disc and AMP organization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HH family members are modified by both cholesterol and long-chain fatty acid modifications [46][47][48] and WNT family members harbor a palmitoylation modification [49,50]. A recent study on FGF transport in the Drosophila wing imaginal disc revealed that the Bnl/ FGF is GPI-anchored to the producing-cell membrane, requiring direct contact with receiving cells to activate signaling through its receptor Breathless (Btl) [51]. These observations, along with the inability of passive diffusion models to fully account for the stringency and robustness observed across physiological morphogen gradients, suggest a requirement for a mode of direct, contact-mediated morphogen delivery to target cells [52][53][54].…”
Section: Overviewmentioning
confidence: 99%